A Comparative Study of Nasal Parameters Between Bengali And Manipuri Ethnic Groups of Bangladesh - Dutta, Kanta Sree; Chowdhury, Pratik; Dutta, Shantanu; Nur-E-Azam, Nazmun; Chakraborty, Sanjoy Kumar; Ashrafuzzaman, Md (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: One of the methods for determining a person's race, ethnicity and gender is to be familiar with nasal anthropometry. The nasal index determination is one of the most widely utilized anthropometric factors in categorizing human races. To measure and compare average nasal anthropometric measurements between Bengali and Manipuri adult male. Materials and methods: This was a cross sectional observational study. Anthropometric analysis of the nasal characteristics of two Bangladeshi ethnic groups was carried out on 200 respondents, were collected through non probability convenience sampling. 100 were Bengali adult male and 100 were Manipuri adult male. The age of the subject ranged from 18 years to 50 years. Using a spreading caliper, measurements of the nasal height and breadth were made and the nasal index was computed from the results using an unpaired t-test. Results: The collected data was statistically analyzed and the result was showing that there is significant difference of nasal height between Bengali (MEAN ± standard deviation) (5.20 cm ± 0.29 cm) and Manipuri male (4.66cm ± 0.23) and Nasal breadth were found as (3.19 cm ±0.19cm) and (3.5cm ± 0.19cm) with p value < 0.001 respectively. Mean nasal index for Bengali (61.41 ± 3.23) and Manipuri (75.12 ± 3.38) were found statistically significant. Bengali and Manipuri male have leptorrhine and mesorrhine type of nose respectively. Conclusion: The attempt provided some baseline data for comparative evaluation of nasal parameters between Bengali and Manipuri adult male, that might be used in different future research and clinical purposes like planning for nasal surgery and cosmetology. JCMCTA 2023 ; 34 (2) : 89-94